The larger mammal fauna from the Lower Paleolithic Schöningen Spear site and its contribution to hominin subsistence. Issue 89 (December 2015) - Van Kolfschoten, Thijs; Buhrs, Elfi; Verheijen, Ivo
Abstract: The locality Schöningen (Germany) is an important source of knowledge about Lower Paleolithic hominin subsistence. The locality includes a series of sites dated to the late Middle Pleistocene with a Holsteinian (MIS 11) and Reinsdorf Interglacial (MIS 9) age. One of the youngest sites is Schöningen 13 II-4, the Spear Horizon site also known as the Horse Butchery site. The organic remains excavated here are exceptionally well-preserved as they were embedded in anaerobic, waterlogged sediments in an area where the groundwater is rich in calcium carbonate. The fossil assemblage is ideal for the study of patterns in hominin interference with the mammalian species encountered at the site. The vertebrate record is extensive and very diverse. The fossil larger carnivore guild of the Spear Horizon faunal assemblage includes saber-toothed cat, fox, and wolf. Herbivores are represented by an elephant species, two equid species, two rhinoceros species, two cervid species, and two large bovid species. Evidence of hominin interference presents itself as either marks on skeletal remains related to the use of bones as knapping tools or hammers, or as marks that indicate butchering activities such as skinning, dismembering, defleshing, filleting, and marrow extraction. The humerus of the saber-toothed cat clearly shows that the bone has been used as a knapping tool. The fossil remains of the other larger carnivores do not show any signs of hominin interference or exploitation. This also applies to the limited number of elephant and rhinoceros remains found at the site. The large horse Equus mosbachensis dominates the larger mammal record and played a major role in hominin subsistence. Marks on the horse bones indicate that a large number of carcasses have been butchered. Traces on the fossil remains of both red deer ( Cervus elaphus ) and the large bovids also indicate exploitation by Lower Paleolithic hominins.